2022
DOI: 10.1038/s41598-022-13544-z
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale placenta DNA methylation integrated analysis reveals fetal sex-specific differentially methylated CpG sites and regions

Abstract: Although male–female differences in placental structure and function have been observed, little is understood about their molecular underpinnings. Here, we present a mega-analysis of 14 publicly available placenta DNA methylation (DNAm) microarray datasets to identify individual CpGs and regions associated with fetal sex. In the discovery dataset of placentas from full term pregnancies (N = 532 samples), 5212 CpGs met genome-wide significance (p < 1E−8) and were enriched in pathways such as keratinization (… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 73 publications
(84 reference statements)
4
7
0
Order By: Relevance
“…The sex differences in DNA methylation levels we observed within the placenta were consistent with those observed in humans, in that male placentas typically exhibited higher methylation levels at DMRs than female placentas (24, 58). Interestingly, it is the opposite of what occurs in most somatic tissues, where sex-associated DMRs tend to be more highly methylated in females (5963).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The sex differences in DNA methylation levels we observed within the placenta were consistent with those observed in humans, in that male placentas typically exhibited higher methylation levels at DMRs than female placentas (24, 58). Interestingly, it is the opposite of what occurs in most somatic tissues, where sex-associated DMRs tend to be more highly methylated in females (5963).…”
Section: Discussionsupporting
confidence: 86%
“…Importantly, these studies provide evidence that placental DNA methylation profiles can predict brain DNA methylation profiles-and possibly the risk of neurodevelopmental disorders. The sex differences in DNA methylation levels we observed within the placenta were consistent with those observed in humans, in that male placentas typically exhibited higher methylation levels at DMRs than female placentas (24,58). Interestingly, it is the opposite of what occurs in most somatic tissues, where sex-associated DMRs tend to be more highly methylated in females (59)(60)(61)(62)(63).…”
Section: Discussionsupporting
confidence: 85%
“…These results could suggest some sex specificities in terms of DNA methylation marks, both at individual CpG and regional levels, with regards to child emotional and behavioral symptoms at 3 years of age. Sexual dimorphism of the placental methylome [22,38,[60][61][62] and of the brain structure and function development [63,64] has been widely documented. Placental dimorphism could be due to distinct effects of sexual hormones and chromosomes [65].…”
Section: Discussionmentioning
confidence: 99%
“…Consistently, human placental DNA methylation of the HSD11B2, NR3C1, and HTR2A genes-involved in the HPA and the serotonin pathways-has been shown to be associated with infant neurodevelopment in humans [23]. Males and females present differences in placental DNA methylation levels as well as in the prevalence of behavioral and emotional disorders in childhood [38][39][40], raising the need to explore sex-specific associations.…”
Section: Introductionmentioning
confidence: 96%
“…Males and female fetuses have been shown to differ in terms of placental DNAm 29,30 as well as in their ability to adapt to adverse intrauterine environments 31,32 . In the ART studies, it has been shown that males have a higher risk to be LGA compared to females [33][34][35] , but still only a few sex-specific EWASs have been performed so far 12,18,22 .…”
Section: Introductionmentioning
confidence: 99%